Advaita a contemporary critique - Srinivasa Rao.; Indian Council of Philosophical Research (New Delhi ; Oxford : Oxford University Press, 2012)
Advaita has been extensively studied by various schools of philosophy in classical India. Srinivasa Rao supplements classical analysis with many special concepts & techniques used in contemporary Western logic & analytic philosophy.
Published in association with the Indian Council of Philosophical Research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Advaita